Crystal structure of N,N-diphenylformamide, C13H11NO - Hosten Eric C.; Betz Richard (Zeitschrift für Kristallographie - New Crystal Structures, 2021)
C13H11NO, orthorhombic, Pca21 (no. 29), a = 23.801(4) Å, b = 6.0510(13) Å, c = 7.2677(14) Å, V = 1046.7(3) Å3, Z = 4, Rgt(F) = 0.0335, wRref (F2) = 0.0896, T = 200 K.